THE USAGE OF ENVIRONMENT TO INCREASE THE STUDENTS ACHIEVEMENT IN NATURAL SCIENCE SUBJECT FOR THE 5th GRADE STUDENTS OF PEMBANGUNAN PRIVATE ELEMENTARY SCHOOL TANJUNG MORAWA TAHUN PELAJARAN 2009/2010 - Nurhaty Purnama Sari (Universitas Riau Kepulauan, 2014)
The usage of environment to increase the students achievement in natural science subject for the 5th grade students of Pembangunan Private Elementary School Tanjung Morawa. The objective of this research is to know the increasing students achievement in natural science subject after taught using environment and without using environment as learning sources. The total sample is all the student in 5th grade of Pembangunan Private Elementary School in Tanjung Morawa. The teaching learning process by using environment was done for the experiment class and without using environment for the control class. The data were obtained from the student ability in answering pre-test and post-test (research instrument) after the teaching learning process has done. The results shows that teaching by using environment has better effect than teaching without using environment. It can be seen from the value of the post-test mean (7.93) for the class taught by using environment method. On the other side, the class taught without using the environment method only reach 5.60. The analysis of statistic (t-test) has showned the significant difference between the usage of environment and without the usage of environment (t count 6.51 t table 2.007). From the success of teaching learning process using the environment to increase the students achievement in natural science subject for the 5th grade students of Pembangunan Private Elementay School Tanjung Morawa on the topic of green plant material. So, it can be accepted as a new method in teaching learning process in Elementary School.